Effects of the Service-learning Methodology on the Environmental Behavior of Students from a Private University, Lima, 2022 (LACCEI, 2024)
The article aims to evaluate the effect of the Service Learning methodology on environmental behavior in students of a private university in Lima, in the 2022-2 semester. The methodology was of an explanatory type, with a quasi-experimental design, with post-test only and intact groups. The sample consisted of two groups, one control and the other experimental, with 80 students in each group, to whom a validated questionnaire was applied as an instrument. with Cronbach's alpha, with 24 questions on a Likert scale, and they measure the environmental behavior variable, with its three dimensions: Eco-efficient practices, Preservation and conservation of the environment, and Environmental sensitivity. The results indicate that the experimental group managed to raise the environmental behavior in its three dimensions and generally obtained two levels, the average and the high, without obtaining low levels. It is concluded in the inferential analysis, of the total instrument, that there are significant differences in the environmental behavior variable, between the mean of the control group (77.90) with respect to the experimental group (95.30) with the Service-Learning methodology. And in the descriptive analysis, it was obtained in the three dimensions for the experimental group, which reach average and high percentages in the students' grades.